Climate change and infectious livestock diseases: The case of Rift Valley fever and tick-borne diseases - Bett, Bernard K.; Lindahl, Johanna F.; Grace, Delia (Springer, 2019)
Climate change influences the occurrence and transmission of a wide range of livestock diseases through multiple pathways. Diseases caused by pathogens that spent part of their life cycle outside the host (e.g. in vectors or the environment) are more sensitive in this regard, compared to those caused by obligate pathogens. In this chapter, we use two well-studied vector-borne diseases—Rift Valley fever (RVF) and tick-borne diseases (TBDs)—as case studies to describe direct pathways through which climate change influences infectious disease-risk in East and southern Africa. The first case study demonstrates that changes in the distribution and frequency of above-normal precipitation increases the frequency of RVF epidemics. The second case study suggests that an increase in temperature would cause shifts in the spatial distribution of TBDs, with cooler and wetter areas expected to experience heightened risk with climate change. These diseases already cause severe losses in agricultural productivity, food security and socio-economic development wherever they occur, and an increase in their incidence or geographical coverage would intensify these losses. We further illustrate some of the control measures that can be used to manage these diseases and recommend that more research should be done to better understand the impacts of climate change on livestock diseases as well as on the effectiveness of the available intervention measures.